Safety and immunogenicity of the PRAME cancer immunotherapeutic in metastatic melanoma: results of a phase I dose escalation study - Gutzmer, Ralf; Utikal, Jochen (ESMO open, 2016)
Purpose: The PRAME tumour antigen is expressed in several tumour types but in few normal adult tissues. A dose-escalation phase I/II study (NCT01149343) assessed the safety, immunogenicity and clinical activity of the PRAME immunotherapeutic (recombinant PRAME protein (recPRAME) with the AS15 immunostimulant) in patients with advanced melanoma. Here, we report the phase I dose-escalation study segment. Patients and methods: Patients with stage IV PRAME-positive melanoma were enrolled to 3 consecutive cohorts to receive up to 24 intramuscular injections of the PRAME immunotherapeutic. The RecPRAME dose was 20, 100 or 500 µg in cohorts 1, 2 and 3, respectively, with a fixed dose of AS15. Adverse events (AEs), including predefined dose-limiting toxicity (DLT) and the anti-PRAME humoral response (ELISA), were coprimary end points. Cellular immune responses were evaluated using in vitro assays. Results: 66 patients were treated (20, 24 and 22 in the respective cohorts). AEs considered by the investigator to be causally related were mostly grade 1 or 2 injection site symptoms, fatigue, chills, fever and headache. Two DLTs (grade 3 brain oedema and proteinuria) were recorded in two patients in two cohorts (cohorts 2 and 3). All patients had detectable anti-PRAME antibodies after four immunisations. Percentages of patients with predefined PRAME-specific-CD4+T-cell responses after four immunisations were similar in each cohort. No CD8+ T-cell responses were detected. Conclusions: The PRAME immunotherapeutic had an acceptable safety profile and induced similar anti-PRAME-specific humoral and cellular immune responses in all cohorts. As per protocol, the phase II study segment was initiated to further evaluate the 500 µg PRAME immunotherapeutic dose. Trial registration number NCT01149343, Results.